Kompos, Sebagai Langkah Inovatif Sekaligus Solusi Green Economy Guna Pemberdayaan Ekonomi Rumah Tangga Berkelanjutan di Kecamatan nan Sabaris, Kabupaten Padang Pariaman - Susanti, Dessi; L. V, Yuhendri; Lestari, Tuti; Armiati, Armiati; Rahmidani, Rose (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to: a) Workshop and assistance in processing cow dung into compost as a green economy solution in order to empower the economy of farmer households, b) Workshop and assistance in using compost grinding machines to produce better quality compost. The series of workshop activities took place in August 2024. The partners of this activity were farmers who were members of farmer groups in Jambak Sunua Barat Village, Nan Sabaris District, Padang Pariaman with 10 participants. This workshop activity received support from the Head of the Farmer Group, the Nagari Government, and the Nan Sabaris District. At that time, the participants of the activity also had high motivation and were very enthusiastic about participating in the workshop so that the activity was followed seriously. The results of this activity showed an increase in the ability of farmer groups as workshop participants and assistance in processing cow dung into compost as well as the use of compost grinding machines to produce better quality compost.